CONCEPTUAL MODEL FOR THE PROFESSIONAL DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION TEACHERS BASED ON PEDAGOGICAL CONTENT KNOWLEDGE AND REFLECTIVE PRACTICE - Rafani Azzam, Gattan; Nuraina Thahira, Amisha; Fakhrun Nizar, M. Akmal; Mursidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The professional development of Islamic Religious Education (PAI) teachers continues to encounter obstacles in the integration of pedagogical competencies with critical reflection, which leads to learning that is less adaptive to the dynamics of modern education and is partial. The necessity of a conceptual paradigm that can systematically connect the dimensions of knowledge and reflective practice is suggested by this condition. It is the objective of this research to establish a conceptual framework for the professional development of PAI instructors that is founded on reflective practice and Pedagogical Content Knowledge (PCK). Using library research, the research employs a qualitative approach that involves the analysis and synthesis of pertinent literature. According to the research findings, the integration of reflective practice and PCK results in a professional development model that is holistic, dynamic, and cyclical. PCK serves as the cognitivepedagogical foundation, while reflection functions as an evaluative mechanism for continuous improvement. Teachers can cultivate learning that is more contextual, adaptive, and meaningful through the implementation of this model. The theoretical contributions of this research enrich the study of teacher professionalism, while also having practical implications for policymakers, educational institutions, and teachers in the development of more sustainable and effective professional development strategies.